Tolerant location detection in sensor networks - Junnila Ville; Laihonen Tero (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2022)
Location detection in sensor networks can be handled with so called identifying codes. For an identifying code to work properly, it is required that no sensors are malfunctioning. Previously, malfunctioning sensors have been typically coped with robust identifying codes. However, they are rather large and, hence, imply high signal interference and energy consumption. To overcome these issues, collections of disjoint identifying codes have been proposed for coping with malfunctioning sensors. However, these collections have some problems regarding detection of malfunctioning sensors and, moreover, it seems unnecessary to restrict oneself to disjoint codes. In this paper, we discuss a certain type of identifying codes, for which the detection of malfunctioning sensors is easy, and based on these codes we design a collection of codes tolerant against malfunctions. We present some results on general graphs as well as optimal constructions in rook's graphs and binary Hamming spaces. (C) 2019 Elsevier Inc. All rights reserved.